POTENSI ANTIMIKROBA EKSTRAK DAUN PUDING HITAM (Grapthophylum pictum L. Griff) TERHADAP PERTUMBUHAN BAKTERI Bacillus subtilis, Lactobacillus rhamnosus DAN JAMUR Malassezia globosa DENGAN METODE KLT-BIOAUTOGRAFI - Faroliu, Goldha; Afara, Rahcmatul (Jurnal Inkofar, 2025)
ABSTRACTGrapthophylum pictum L. Griff or Handeuleum Leaf is a plant that is widely cultivated in Indonesia for its leaves. The flavonoid, phenolic, steroid and terpenoid compounds contained in the ethanol extract of Handeuleum Leaf has antimicrobial activity. The aim of this study was to determine the results of phytochemical screening and their antimicrobial activity. The Handeuleum leaf extraction process is carried out using the maceration method, then identifying the compounds using the TLC method. The TLC results showed that there were active compounds in Grapthophylum pictum L. Griff in the form of flavonoids, phenols, steroids and terpenoids. Testing antimicrobial activity using the TLC-Bioautography method against Bacillus subtilis bacteria at a concentration of 30% found all compounds. And the bacteria Lactobacilus rhamnnosus at a concentration of 30% in compounds 1, 2, 6, 7, and 8 showed antibacterial activity, while compounds 3, 4, and 5 did not show antibacterial activity. Meanwhile, against the fungus Malassezia globosa at a concentration of 30%, compounds 1, 2 and 3 showed antifungal activity and compounds 4, 5, 6, 7 and 8 did not show antifungal activity.